Evaluating Nurses’ Perceptions Toward Lifelong Learning And Its Impact On Patient Care (The Review of Diabetic Studies, 2025)
Background: Lifelong learning is a qualitative indicator in nursing, enhancing nurses' capacity and skills to meet healthcare demands and improve patient outcomes.Objective: This study aimed to assess nurses’ perceptions of lifelong learning and examine its impact on clinical practice and patient care at King Abdullah bin Abdulaziz University Hospital in Riyadh, Saudi Arabia.Methods: A cross-sectional study was conducted between July and September 2025. The sample of the study consisted of 495 nurses. Data were collected through an electronic questionnaire adapted from the Q-PDN and relevant literature. SPSS 23 statistical software platform was used for statistical analysis.Results: Nurses demonstrated strong positive perceptions of lifelong learning (overall mean = 4.24 ± 0.96) and high motivation to participate in these activities (mean = 4.18 ± 0.93), especially when supported by colleagues and management. Workshops and in-hospital training were described as the most effective learning tools (mean = 4.44 ± 0.85). Key barriers included incompatibility of educational content, workload, and time constraints. Regression analysis showed a significant positive relationship between lifelong learning and patient care (β = 0.684, R² = 0.226, p < 0.001).Conclusion: Nurses value the importance of lifelong learning, its importance in enhancing their clinical skills and keeping up with scientific studies and modern nursing care methods, which positively impacts patient care.